Possibilities of attentional control of pain: Influence of distractive Stroop task on pain threshold and pain tolerance - Ivanec, Dragutin (Array, 2006)
Attention has been shown to modulate pain perception, but the relationship between attention and pain perception is still not clearly understood. Two independent experiments were conducted to examine the influence of focusing attention away from painful stimulation on the pain threshold and pain tolerance. In Experiment I (37 female participants) the dependent variable was pain threshold, and in Experiment II (42 female participants) the dependent variable was pain tolerance. Distraction task was classic color-based Stroop task. Each participant participated in two experimental situations. In one experimental situation participants were experiencing noxious (painful) stimulation while doing the Stroop task, and in the other experimental situation that stimulation was not accompanied with the additional distraction task. The results show no analgesic effect of focusing attention away form painful stimulation on either pain threshold or pain tolerance. The results are not consistent with the results obtained in similar studies on the influence of attention on pain perception. Possible explanations for these results are based upon different methodological approaches and upon the importance of interaction between various psychological factors in pain perception, with the emphasis given on the expectation that distraction strategy will be effective in modulating pain perception.